2017
DOI: 10.3389/fnhum.2017.00470
|View full text |Cite
|
Sign up to set email alerts
|

Importance Modulates the Temporal Features of Self-Referential Processing: An Event-Related Potential Study

Abstract: A growing number of studies have demonstrated preferential processing of self-related information. However, previous research has been limited in examining the distinction between processes related to the self and those related to the non-self, it remains unclear how self-related information with differing levels of importance is processed within the self. The present study examined how the importance of self-related content affects the neural activity involved in self-referential processing. The behavioral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
(75 reference statements)
2
10
0
Order By: Relevance
“…These results are in line with previous research (Keyes et al., 2010; Knyazev, 2013; Miyakoshi et al., 2010; Sui et al., 2006; Xu et al., 2017). Studies on the neural underpinnings of self‐relevant processing have suggested that the larger the long‐lasting positivity, the more important is the self‐related content (Anaki & Bentin, 2009; Chen et al., 2011; Muñoz et al., 2020; Tacikowski & Nowicka, 2010; Xu et al., 2017). In other words, larger amplitudes in later components might reflect the increased allocation of attention, and more elaborate processing, presumably due to the meaningfulness of self‐relevant information.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in line with previous research (Keyes et al., 2010; Knyazev, 2013; Miyakoshi et al., 2010; Sui et al., 2006; Xu et al., 2017). Studies on the neural underpinnings of self‐relevant processing have suggested that the larger the long‐lasting positivity, the more important is the self‐related content (Anaki & Bentin, 2009; Chen et al., 2011; Muñoz et al., 2020; Tacikowski & Nowicka, 2010; Xu et al., 2017). In other words, larger amplitudes in later components might reflect the increased allocation of attention, and more elaborate processing, presumably due to the meaningfulness of self‐relevant information.…”
Section: Discussionsupporting
confidence: 93%
“…Our results support that the N170 is insensitive to an effect of face familiarity. This is in accordance with previous works (Alzueta et al., 2019; Butler et al., 2013; Kotlewska & Nowicka, 2015; Miyakoshi et al., 2008, 2010; Sui et al., 2006; Tanaka et al., 2006; Xu et al., 2017). In turn, this pattern is consistent with the proposal that the N170 reflects an automatic mechanism detecting the global configuration of a face in a recognition task, rather than identifying the identity of a face (Olivares et al., 2015; Schweinberger & Neumann, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The P2 component is related to the detection of emotionally significant stimuli, and increased P2 amplitudes reflect more attention resource allocation to these stimuli (Yuan et al, 2010;Carretié et al, 2011). In addition, the P2 component was found to be influenced by the extent of self-relevance and the importance of self-relevant content (Chen et al, 2011;Fan et al, 2013;Xu et al, 2017). For example, a previous ERP study showed that self-name (higher self-relevance) induced increased P2 amplitudes than lower self-relevance and nonself-relevant name stimuli (Fan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%